Outcomes of Total Knee Replacement after Patellofemoral Arthroplasty - Hutt, Jonathan; Dodd, Matthew; Bourke, Henry; Bell, Jonathan (The Journal of Knee Surgery, 2013)
There is increasing interest in the use of patellofemoral joint replacements and the cohort receiving them are the youngest of any of the groups of patients undergoing a knee arthroplasty. With more contemporary prostheses, progression of arthritis in other parts of the knee joint is becoming the predominant mechanism of failure. We conducted a multicenter retrospective comparative cohort study to discover whether the outcome of total knee replacement is compromised by prior patellofemoral joint arthroplasty. A total of 21 patients with a mean age of 61 years, who were revised from a patellofemoral joint replacement to a total knee replacement, were compared with a matched cohort of patients who underwent primary total knee replacement. At a mean follow-up of 2.4 years, the primary total knee replacement cohort had significantly better Oxford Knee Scores, Western Ontario and McMaster Universities Osteoarthritis Index (WOMAC) function scores, pain visual analog scores, and EQ–5D scores. There was no significant difference in patient satisfaction or EQ–5D visual analog scale.Our results indicate that although the revision of a patellofemoral joint replacement to a total knee replacement is a technically straightforward procedure, the eventual outcome may be less satisfactory when compared with a primary total knee replacement.
Keywords: patellofemoral; arthroplasty; revision; outcomes